UN Natural Resources and Other Sanctions: Who Benefits? - Carisch, Enrico; Rickard-Martin, Loraine (Social Research)
The article examines the United Nations (UN) Security Council's commodity sanctions and asset freezes and other groups' advocacy as of December 2015. The sanctions' objectives, methods, and motivations are reportedly not assessed as they are deemed to be beneficial for the common good. It analyzes sanctions as an agent of change, the UN's intervention on Cambodia and Angola, and the UN's problems in cutting the diamond revenues of guerilla group União Nacional para a Independência Total de Angola. Also discussed are the commodity wars in Sierra Leone, the Congo, and Liberia.